Freshwater gastropod community in South Konawe District, Southeast Sulawesi, Indonesia - DEDY OETAMA; MUHAMMAD FAJAR PURNAMA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Oetama D, Purnama MF. 2022. Freshwater gastropod community in South Konawe District, Southeast Sulawesi, Indonesia. Biodiversitas 23: 3364-3372. The freshwater gastropod population in South Konawe District, Southeast Sulawesi, Indonesia, consists of aquatic and terrestrial snail communities. This resource (gastropod) is an ecological and economic potential that needs to be maintained and utilized optimally and sustainably. This research was conducted in April-July 2021 and aimed to determine the ecological index of the inland gastropod community in the South Konawe District. The sampling location was determined qualitatively using the purposive sampling method and a simple random sampling technique (Quantitative based). Gastropod samples were collected manually (hand picking) with a paralon pipe (3.5 inches), Sieve (1 mm), and Gloves. The total gastropods obtained at 33 sampling locations in this district were 2635 individuals. The inland gastropods comprised 19 genera and 33 species spread over 9 families, namely Achantinidae, Ampullariidae, Ariophantidae, Lymnaeidae, Neritidae, Pachychilidae, Planorbidae, Thiaridae, and Viviparidae. The average abundance of gastropods reached 79.85 ind./m2 and the abundance of gastropod species ranged from 0.58-13.48 ind./m2. Overall, the analysis of gastropod ecology index showed a stable condition, where the diversity of gastropod species was categorized as high (H'= 3.03), moderate evenness (E= 0.87), and high species richness (R= 4.06). There were no dominant species (C= 0.08) and the gastropod distribution showed a clustered pattern (Ip= 0.02). These ecological index values indicated that the gastropod community in the inland waters of South Konawe District was in a stable condition. Although the gastropod community in the inland waters of the South Konawe District simultaneously has the same area as the invasive gastropod from the family Thiaridae, namely Melanoides tuberculata (O.F.Müller, 1774) and Tarebia granifera (Lamarck, 1816).